Epoxy resin composition, prepreg, laminated board and metal foil-clad laminated board

By introducing amino-modified silicone polymer into the epoxy resin system and co-curing the epoxy resin to co-cure the epoxy resin, the limitations of the traditional system in terms of heat resistance and toughness are solved, and higher thermal stability and toughness are achieved.

CN119661982APending Publication Date: 2025-03-21JIANGXI SHENGYI TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411974075.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Traditional epoxy resin systems have limitations in terms of heat resistance and toughness, and it is difficult to meet the needs of high-performance laminated copper plates.

Method used

By introducing amino-modified silicone polymer into the epoxy resin system, the epoxy resin is co-cured to increase the overall cross-linking density, and combining epoxy resins with different molecular weights to improve the heat resistance and toughness of the system.

Benefits of technology

The heat resistance and toughness of epoxy resin are improved, and the limitations of traditional systems in these aspects are solved, so as to achieve better thermal stability and high toughness effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005220035670000051
    Figure BDA0005220035670000051
  • Figure BDA0005220035670000081
    Figure BDA0005220035670000081
  • Figure BDA0005220035670000091
    Figure BDA0005220035670000091
Patent Text Reader

Abstract

The invention provides an epoxy resin composition, a prepreg, a laminated board and a metal foil-clad laminated board. The epoxy resin composition comprises the following components in parts by weight: A, 100 parts of epoxy resin; b, 120-390 parts of a curing agent; c, 50 to 200 parts of inorganic filler; the curing agent comprises B1 amino modified organosilicon polymer and B2 amine curing agent and / or phenolic curing agent, and the ratio of B1 to B2 is (1: 2)-(1: 7). The amino modified organic silicon and the amine and / or phenolic aldehyde curing agent are compounded to co-cure the epoxy resin, the overall crosslinking density is increased, and meanwhile, compounding of epoxy resin with different molecular weights is combined, so that the effect of increasing the heat resistance and toughness of a system is achieved. Meanwhile, an amino modified organosilicon polymer is introduced into an epoxy resin system, so that the soft degree of a curing molecular chain can be adjusted, the release of stress in the resin curing process is accelerated, and the effect of flatness of the surface of the prepreg and the plate is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laminated boards, and relates to an epoxy resin composition, a prepreg, a laminated board and a metal foil-clad laminated board. Background Art

[0002] Epoxy resin is widely used in electronic packaging, copper clad laminates, composite materials and other fields due to its excellent adhesion, chemical resistance, electrical insulation and mechanical properties. With the rapid development of the electronics industry, the requirements for laminated copper clad laminates are getting higher and higher, especially in terms of stress buffering, heat resistance, flatness and other aspects. Traditional epoxy resin systems have certain limitations in terms of heat resistance and toughness, and it is difficult to meet the needs of high-performance laminated copper clad laminates. In order to improve the performance of epoxy resin, various curing agents are modified, such as amine curing agents, phenolic curing agents, etc., but a single curing agent is often difficult to meet multiple performance requirements, and silicone oil generally only serves as some auxiliary agents such as surface wetting and leveling agents. How to reasonably select and match to achieve a balance between performance and processability is a technical difficulty.

[0003] CN111647253A discloses a copper-clad laminate with low thermal expansion coefficient and a preparation method thereof, wherein the copper-clad laminate is made of glass fiber cloth impregnated with an impregnation liquid as a semi-cured sheet copper foil; the raw material components of the impregnation liquid include, by weight: 30-40 parts of modified silicone oil, 50-60 parts of epoxy resin, 100-200 parts of organic solvent, 0.2-0.8 parts of catalyst, 5-10 parts of curing agent, and 50-200 parts of inorganic filler. The invention mainly provides a preparation method of the copper-clad laminate with low thermal expansion coefficient, but does not solve the actual problems of heat resistance and toughness.

[0004] Therefore, in this field, how to solve the problems of heat resistance and toughness remains the focus of research. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide an epoxy resin composition, a prepreg, a laminate and a metal foil-clad laminate.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In one aspect, the present invention provides an epoxy resin composition, comprising the following components in parts by weight:

[0008] A. 100 parts of epoxy resin;

[0009] B. 120-390 parts of curing agent;

[0010] C. 50-200 parts of inorganic filler;

[0011] Wherein, the curing agent comprises: B1 amino-modified silicone polymer, B2 amine curing agent and / or phenolic curing agent, and the weight ratio of B1 to B2 is 1:2 to 1:7.

[0012] The molecular structure of the epoxy resin and curing agent composition contains a large number of aromatic structures, and the molecular chain is relatively rigid. In addition, the local stress of this type of resin cured product is relatively large. Excessive local stress of the resin cured product can cause prepregs and copper-clad laminates to warp and deform in high-density interconnection applications of thin media, resulting in problems such as poor expansion and contraction and insufficient reliability. Introducing amino-modified silicone polymers into the epoxy resin system can adjust the softness of the cured molecular chain, accelerate the release of stress during the resin curing process, and participate in the reaction as a co-curing agent to improve the heat resistance of the system.

[0013] The present invention adopts amino-modified silicone polymer and amine and / or phenolic curing agent to compound and co-cure epoxy resin to increase the overall crosslinking density, and at the same time combines with epoxy resin to achieve the effect of increasing the heat resistance and toughness of the system to solve the above-mentioned problems.

[0014] Preferably, the epoxy resin is a combination of a BPA epoxy resin with a weight average molecular weight of 800-10000, a phenol type epoxy resin with a weight average molecular weight of 1000-10000 and other epoxy resins with a weight average molecular weight of 11000-30000.

[0015] In the present invention, the three types of epoxy resins mentioned above are selected for combination. BPA epoxy resin (MW 800-10000) has the characteristics of high Tg and good heat resistance, which is conducive to better stability at high temperature and reduces the deformation and stress increase of electronic circuit boards under heat. Phenol epoxy resin (MW 1000-10000) and other epoxy resins (MW 11000-30000) can be well matched with BPA epoxy resin for close crosslinking and curing due to their unique crosslinking density, achieving better thermal stability and high toughness.

[0016] In the present invention, the weight average molecular weight of the BPA epoxy resin is 800-10000, such as 800, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000 or 10000. If the weight average molecular weight of the BPA epoxy resin used in the present invention is too high, the resin solubility is poor, the reactivity is slow, resulting in a rough surface of the bonding sheet and a low Tg of the board. In the present invention, the weight average molecular weight of the phenol type epoxy resin is 1000-10000, for example, it can be 1000, 5000, 8000, 10000, 20000, 23000, 25000, 28000 or 30000. If the weight average molecular weight of the phenol type epoxy resin is too low, the crosslinking density and Tg are low. If the weight average molecular weight of the phenol type epoxy resin is too high, the appearance of the bonding sheet is poor and the reaction is slow, resulting in insufficient curing.

[0017] In the present invention, the weight average molecular weight of the other epoxy resin is 11000-30000, for example, it can be 10001, 15000, 18000, 20000, 23000, 25000, 28000 or 30000. If the weight average molecular weight of the other epoxy resin is too low, the crosslinking density and Tg will be low. If the weight average molecular weight of the other epoxy resin is too high, the resin compatibility will be poor and the bonding sheet will be rough.

[0018] Preferably, the other epoxy resin is selected from one or a combination of at least two of bisphenol A epoxy resin, bisphenol S epoxy resin, and bisphenol F epoxy resin having a weight average molecular weight of 11,000-30,000.

[0019] In the present invention, the weight percentage of the BPA epoxy resin in the epoxy resin is 60wt%-80wt%, for example, 60wt%, 65wt%, 68wt%, 70wt%, 75wt%, 78wt% or 80wt%, the weight percentage of the phenol-type epoxy resin is 10-20%, for example, 10%, 12%, 14%, 15%, 18% or 20%; the weight percentage of the other epoxy resins is 10-20%, for example, 10%, 12%, 14%, 15%, 18% or 20%.

[0020] In the present invention, relative to 100 parts of epoxy resin A, the amount of curing agent B is 120-390 parts, for example, it can be 120 parts, 150 parts, 180 parts, 200 parts, 250 parts, 280 parts, 300 parts, 330 parts, 350 parts or 390 parts.

[0021] The amount of curing agent used is generally to form a cross-linking network with the epoxy resin. Too low a dosage will result in insufficient curing, but too much will cause a too-fast reaction, making the board brittle and causing quality abnormalities inside the substrate.

[0022] In the present invention, the weight ratio of B1 to B2 in the curing agent is 1:2 to 1:7, for example, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5 or 1:7.

[0023] The amino-modified silicone polymer of the present invention can improve the poor compatibility between the phenolic epoxy resin and the curing agent B2. The side chain amino-modified silicone polymer can improve the compatibility and reactivity between the resin and reduce the migration problem of the amino-modified silicone polymer. It also promotes the cross-linking reaction between the amino-modified silicone polymer and the epoxy resin system, so that the amino-modified silicone polymer molecular chain is introduced into the cross-linked network of the epoxy resin, increasing the flexibility of the network, thereby accelerating the release of stress during the curing process and achieving the effect of high heat resistance. If the proportion of B1 is too large, the cross-linking density will be too brittle, and if the proportion is too low, the effect of high heat resistance cannot be achieved.

[0024] In the present invention, the inventors found that in addition to amino-modified silicone polymers, silicone polymers modified with other groups such as epoxy, vinyl, etc., do not have as significant heat resistance as the amino-modified group.

[0025] In the present invention, the amino-modified silicone polymer is a side chain amino-modified silicone polymer.

[0026] Preferably, the functional group equivalent of the side chain amino-modified silicone polymer is ≤1000 g / mol, for example 1000 g / mol, 900 g / mol, 800 g / mol, 600 g / mol, 400 g / mol, 200 g / mol, 100 g / mol, 80 g / mol, 50 g / mol, etc.

[0027] Preferably, the structure of the side chain amino-modified silicone polymer is as follows:

[0028]

[0029] Wherein R1 and R2 are independently selected from at least one of RNH2, RNR'NH2, R is methyl, ethyl or a longer carbon chain, R' is a C1-C10 alkyl group (e.g., methyl, ethyl, etc.); m and n are integers of 5-100 (e.g., 5, 8, 10, 12, 15, 18, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100).

[0030] Preferably, the viscosity of the amino-modified silicone polymer at 25°C is 50-1000 mm 2 / s, for example 50mm 2 / s, 80mm 2 / s、100mm 2 / s、300mm 2 / s、500mm 2 / s、800mm 2 / s or 1000mm 2 / s, etc.

[0031] Preferably, the amine curing agent includes one or a combination of at least two of aromatic amine compounds or dicyandiamide compounds.

[0032] Preferably, the phenolic curing agent includes one or a combination of at least two of linear phenolic resin, phosphorus-containing phenolic resin or nitrogen-containing phenolic resin.

[0033] Preferably, the inorganic filler includes any one of silicon dioxide, aluminum oxide, talc, boehmite, mica, calcined kaolin, aluminum hydroxide, magnesium hydroxide, zinc oxide, titanium oxide, boron nitride, calcium carbonate, barium sulfate, barium titanate, aluminum borate, potassium titanate, E glass powder, S glass powder, D glass powder or hollow glass rod, or a mixture of at least two thereof.

[0034] In the present invention, relative to 100 parts of epoxy resin A, the amount of the inorganic filler C is 50-200 parts, for example, 50 parts, 80 parts, 100 parts, 120 parts, 150 parts, 180 parts or 200 parts.

[0035] In the present invention, the amount of the inorganic filler is 50%wt-200%wt of the total amount of the epoxy resin, preferably 55%wt to 200%wt, and more preferably 60%wt to 200%wt.

[0036] In the present invention, when the filler content is less than 50wt% of the total amount of the epoxy resin, its solid content is too low, affecting the economic efficiency of use and reducing the solvent formulation flexibility of the resin composite; when the filler content is greater than 200wt% of the total amount of the epoxy resin, its solid content is too high, its fluidity is poor, and it cannot be used.

[0037] Preferably, the epoxy resin composition further comprises a curing accelerator.

[0038] Preferably, the accelerator is any one of imidazole compounds, imidazole adducts, peroxides or salts, or a mixture of at least two of them.

[0039] Preferably, the amount of the accelerator is 0.1-25 parts, such as 0.1 parts, 1 parts, 3 parts, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts or 25 parts, relative to 100 parts of epoxy resin. When the amount of the accelerator is less than 0.01wt% of the total amount of the epoxy resin, its reaction is too slow and the curing time is too long, which affects the economic efficiency of use; when the content of the accelerator is greater than 25wt% of the total amount of the epoxy resin, its reaction is too fast, and the index of the semi-cured sheet cannot be controlled during gluing, and it cannot be used.

[0040] On the other hand, the present invention provides a resin adhesive, which is obtained by dissolving or dispersing the thermosetting resin composition as described above in a solvent.

[0041] In another aspect, the present invention provides a prepreg comprising a reinforcing material, and the thermosetting resin composition as described above attached to the reinforcing material after impregnation and drying.

[0042] In another aspect, the present invention provides a laminate comprising one or at least two laminated prepregs as described above.

[0043] In another aspect, the present invention provides a metal foil-clad laminate comprising one or at least two stacked prepregs provided by the third aspect of the present invention and metal foils covering one or both sides of the outer side of the prepregs.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] The present invention uses amino-modified silicone and amine and / or phenolic curing agents to compound, co-cure epoxy resin, increase the overall crosslinking density, and combine with epoxy resins of different molecular weights to increase the heat resistance and toughness of the system. At the same time, the amino-modified silicone polymer introduced into the epoxy resin system can also adjust the softness of the cured molecular chain and accelerate the release of stress during the resin curing process, thereby achieving the effect of smooth surface of the prepreg and the plate. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0047] Example 1

[0048] Mix 70 parts of BPA epoxy resin (Hongchang Electronics 128, weight average molecular weight of 1600), 20 parts of phenol type epoxy resin (Changchun Chemical PNE177, weight average molecular weight of 2000), 10 parts of other epoxy resins (bisphenol A type, Guodu Chemical, YD019C weight average molecular weight of 16000), 140 parts of phenolic resin (Olin, XZ92741), 40 parts of amino modified silicone polymer (Shin-Etsu, KF880), 2 parts of imidazole compound (Shikoku Chemical, 2E4MZ), 180 parts of silicon micropowder (Lianrui New Materials, DS1032A) and an appropriate amount of MEK solvent, stir well to obtain a resin glue with a solid content of 65%.

[0049] The resin composition glue was used to impregnate E-type glass fiber cloth (Honghe Glass Fiber, E1080), and dried at 160° C. for 10 minutes to remove the solvent, thereby obtaining a prepreg with a resin content of about 50%.

[0050] A 1 / 2Oz copper foil is coated on each side of the four overlapping prepregs, and hot pressing is performed at a temperature of 200° C. and a pressure of 3.0 MPa for 60 minutes to obtain a double-sided copper-clad laminate.

[0051] Example 2-15

[0052] The compositions of the resin compositions in Examples 2-15 and Comparative Examples 1-9 are shown in Tables 1-3.

[0053] The weight average molecular weight of the BPA type epoxy resin used in Example 8 is 800 (Hongchang Electronics 128), the weight average molecular weight of the BPA type epoxy resin used in Example 9 is 10000 (Guodu Chemical YD012A80), and the weight average molecular weight of the phenol type epoxy resin used in Example 10 is 1000 (KOLON KEP1130), the weight average molecular weight of the phenol type epoxy used in Example 11 is 10000 (NPPN640), the weight average molecular weight of the macromolecular bisphenol A type epoxy resin used in Example 12 is 11000 (Nan Ya Electronic Materials NPES905), the weight average molecular weight of the macromolecular bisphenol A type epoxy resin used in Example 13 is 30000 (Nan Ya Electronic Materials NPSN610BM50), the weight average molecular weight of the BPA type epoxy used in Comparative Example 5 is 600 (Nan Ya Electronic Materials NPEK050), the weight average molecular weight of the phenol type epoxy is 800 (Nan Ya Electronic Materials NPPN631), the molecular weight of the macromolecular bisphenol A type epoxy resin is 8000 (Nan Ya Electronic Materials NOES901), the weight average molecular weight of the BPA type epoxy used in Comparative Example 6 is 20000 (Guodu Chemical YD017), and the weight average molecular weight of the phenol type epoxy is 20000 (Nanya Electronic Materials NPPN433A70), the molecular weight of the macromolecular bisphenol A epoxy resin is 50000 (Guodu Chemical YD020); the weight average molecular weight of the BPA type epoxy used in Comparative Example 7 is 600 (Nanya Electronic Materials NPEK050), the weight average molecular weight of the phenol type epoxy is 20000 (Nanya Electronic Materials NPPN433A70), the molecular weight of the macromolecular bisphenol A type epoxy resin is 50000 (Guodu Chemical YD020), the weight average molecular weight of the BPA type epoxy used in Comparative Example 8 is 20000 (Guodu Chemical YD017), the weight average molecular weight of the phenol type epoxy is 800 (Nanya Electronic Materials NPPN631), and the molecular weight of the macromolecular bisphenol A type epoxy resin is 8000 (Nanya Electronic Materials NOES901); the B1 silicone polymer used in Comparative Example 9 is a non-branched type (Japan Shin-Etsu, KF8010).

[0054] Except for the raw materials specifically indicated above, the specific selection of other components in Examples 2-15 and Comparative Examples 1-19 is the same as that in Example 1.

[0055] Its performance tests are shown in Tables 1 to 3.

[0056] Table 1

[0057]

[0058]

[0059] Table 2

[0060]

[0061] Table 3

[0062]

[0063]

[0064] illustrate:

[0065] (1) Glue liquid state: Under certain bright light, the uniformity of the glue liquid can be seen by naked eyes, that is, the phase separation and non-phase separation can be identified.

[0066] (2) Appearance of the adhesive sheet: Observe the appearance of the PP under strong light. A score below 60 indicates serious lack of resin; a score between 60 and 79 indicates slight lack of resin; a score between 80 and 89 indicates no obvious lack of resin; and a score of 90 or above indicates no other abnormalities in the appearance of the PP.

[0067] (3) Glass transition temperature: Differential scanning calorimetry (DSC) is used to measure the glass transition temperature according to the DSC method specified in 2.4.25 of IPC-TM-650.

[0068] (4) Heat resistance T288: Measured using a thermomechanical analyzer in accordance with the method specified in IPC-TM-650 2.4.24.1.

[0069] (5) Toughness: Drop Weight Test: Test method: Release a heavy hammer at a certain height to impact the sample and observe whether the sample breaks or cracks. The characterization parameter is the energy threshold for the occurrence of fracture or crack. A score below 60 indicates that the sample is severely fractured or has a deep crack, a score between 60 and 80 indicates that the sample has a slight deep crack, and a score of 80 or above indicates that the sample has a shallow crack.

[0070] From the appearance of the bonding sheet: compared with Examples 1-15, the appearance of the entire bonding sheet in Comparative Examples 1-9 is at a passing level or below.

[0071] From the perspective of board performance: the curing agent ratio used in Comparative Examples 1 and 2 is too low or too high, which will result in poor DSC-Tg and heat resistance and toughness of the boards; the BPA type epoxy resin or phenol type epoxy resin or other macromolecular epoxy resin used in Comparative Examples 3 and 4 is too low or too high, which will result in poor appearance of the bonding sheet, DSC-Tg of the board, heat resistance and toughness; the weight average molecular weight of BPA type epoxy, phenol type epoxy and other macromolecular epoxy used in Comparative Examples 5, 6, 7 and 8 is too low or too high, which will result in poor appearance of the bonding sheet, toughness and heat resistance of the board; the non-side chain amino-modified silicone polymer used in Comparative Example 9 will result in the heat resistance of the board not achieving a good effect.

[0072] The applicant declares that the present invention uses the above embodiments to illustrate the epoxy resin composition, prepreg, laminate and metal foil clad laminate of the present invention, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An epoxy resin composition, characterized in that The epoxy resin composition comprises the following components in parts by weight: A. 100 parts of epoxy resin; B. 120-390 parts of curing agent; C. 50-200 parts of inorganic filler; Wherein, the curing agent comprises: B1 amino-modified silicone polymer, B2 amine curing agent and / or phenolic curing agent, and the weight ratio of B1 to B2 is 1:2 to 1:

7.

2. The epoxy resin composition according to claim 1, characterized in that The epoxy resin is a combination of a BPA epoxy resin with a weight average molecular weight of 800-10000, a phenol type epoxy resin with a weight average molecular weight of 1000-10000 and other epoxy resins with a weight average molecular weight of 11000-30000.

3. The epoxy resin composition according to claim 2, characterized in that The other epoxy resin is selected from one or a combination of at least two of bisphenol A epoxy resin, bisphenol S epoxy resin, and bisphenol F epoxy resin having a weight average molecular weight of 11000-30000; Preferably, the weight percentage of the BPA epoxy resin in the epoxy resin is 60wt%-80wt%, the weight percentage of the phenol type epoxy resin is 10-20%, and the weight percentage of the other epoxy resins is 10-20%.

4. The epoxy resin composition according to any one of claims 1 to 3, characterized in that The amino-modified silicone polymer is a side-chain amino-modified silicone polymer; Preferably, the functional group equivalent of the side chain amino-modified silicone polymer is ≤1000 g / mol; Preferably, the structure of the side chain amino-modified silicone polymer is as follows: Wherein R1 and R2 are independently selected from at least one of RNH2 and RNR'NH2, R is methyl, ethyl or a longer carbon chain, and R' is a C1-C10 alkyl group; wherein m and n are between 5 and 100; Preferably, the viscosity of the amino-modified silicone polymer at 25°C is 50-1000 mm 2 / s.

5. The epoxy resin composition according to any one of claims 1 to 4, characterized in that The amine curing agent includes one or a combination of at least two of an aromatic amine compound or a dicyandiamide compound; Preferably, the phenolic curing agent includes one or a combination of at least two of linear phenolic resin, phosphorus-containing phenolic resin or nitrogen-containing phenolic resin.

6. The epoxy resin composition according to any one of claims 1 to 5, characterized in that The inorganic filler includes any one of silicon dioxide, aluminum oxide, talc, boehmite, mica, calcined kaolin, aluminum hydroxide, magnesium hydroxide, zinc oxide, titanium oxide, boron nitride, calcium carbonate, barium sulfate, barium titanate, aluminum borate, potassium titanate, E glass powder, S glass powder, D glass powder or hollow glass rod, or a mixture of at least two thereof.

7. The epoxy resin composition according to any one of claims 1 to 6, characterized in that The epoxy resin composition also includes an accelerator D; Preferably, the accelerator is any one of imidazole compounds, imidazole adducts, peroxides or metal or organic acid salts, or a mixture of at least two thereof; Preferably, the amount of the accelerator is 0.1-10 parts relative to 100 parts of epoxy resin.

8. A resin glue, characterized in that: The resin glue is obtained by dissolving or dispersing the thermosetting resin composition according to any one of claims 1 to 7 in a solvent.

9. A prepreg, characterized in that: The prepreg comprises a reinforcing material, and the thermosetting resin composition according to any one of claims 1 to 7 attached to the reinforcing material after being impregnated and dried.

10. A metal foil-clad laminate, characterized in that: The metal foil clad laminate comprises one or at least two stacked prepregs according to any one of claims 1 to 7 and a metal foil clad on one or both sides of the outer side of the prepreg.

Citation Information

Cited By

  • High-toughness anti-aging phenolic resin-based copper-clad plate and preparation method thereof

    CN120716296A

  • A high-toughness and aging-resistant phenolic resin-based copper-clad plate and a preparation method thereof

    CN120716296B